An Identification of a Spatial Interaction Towards Rice Import in Selected ASEAN+3 Countries - Ekalia Yusiana; Dedi Budiman Hakim; Tanti Novianti; Yusman Syaukat (HABITAT, 2022)
Rice turns out as significant commodity in order to meet people’s needs of food on a half of the world's population. Rice is the most consumed commodity in Asia and wold, especially countries that are members of the ASEAN+3. The need for rice that is a basic necessity must be met, thus, the supply must be maintained as well to meet the needs of staple food, and every country conducts a trade through import activities. This study aims at examining whether there is a spatial interaction of rice import in the ASEAN+3. The results of the Moran I Test show that there is a spatial interaction on rice import in the ASEAN+3 towards 11 selected countries. Trade groupings (agglomeration) were also identified in the trade area. Identification of trade groupings occurs in several countries regarding countries that are in the low-high quadrant such as Vietnam, Thailand, Republic of Korea and Indonesia.